Nylon composite material resistant to low-temperature falling cracking, preparation method of nylon composite material and nylon product
By using specific types of nylon resins and specific content of toughener, glass fiber and other components in nylon composites, a nylon composite material with excellent crack resistance under low temperature conditions was prepared, and the existing nylon was solved. The problem of insufficient crack resistance at extremely low temperatures.
Patent Information
- Application Number
- CN202411809738.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
Existing nylon materials are difficult to maintain good crack resistance under extremely low temperature conditions, especially in thin-walled applications.
A specific type of nylon resin (such as PA612 or PA66) is used to combine a specific content of toughening agent, glass fiber, antioxidant, light stabilizer and lubricant to prepare a nylon composite material that resists low temperature cracking. The component ratio of this material is: 43 to 60 parts of nylon resin, 8 to 15 parts of toughening agent, 30 to 40 parts of glass fiber, 0.3 to 0.5 parts of antioxidant, 0.3 to 0.5 parts of light stabilizer, 0.5 to 2 parts of Lubricant.
This nylon composite material not only meets the requirements of thin-walled applications, but also shows good crack resistance and impact resistance under low temperature conditions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nylon materials, and in particular to a low-temperature crack-resistant nylon composite material and a preparation method thereof, and nylon products. Background Art
[0002] Nylon material is one of the important engineering plastics. It has high melting point, high rigidity and excellent heat resistance, so it is often used to prepare parts for automobiles, home appliances and aerospace equipment. Common nylon materials mainly include nylon 6, nylon 66, long-chain nylon and high-temperature nylon, among which nylon 6 and nylon 66 are used in the largest amount and have the widest application range.
[0003] With the rapid development of science and technology, higher requirements are put forward for the lightweight of nylon materials. Thin-wall application is one of the important ways to achieve lightweight of nylon materials. For example, the automotive industry generally classifies plastics with a wall thickness of less than 2mm as thin-wall materials, and the lowest wall thickness can even be 0.3mm; therefore, the anti-fall and cracking performance of nylon materials is put forward a higher challenge, especially in the application environment of extremely low temperature weather.
[0004] Therefore, how to make thin-walled nylon materials have good anti-cracking performance under low temperature conditions has become one of the problems to be solved. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a nylon composite material that can be thin-walled and has excellent resistance to low-temperature cracking, a preparation method thereof, and a nylon product comprising the above-mentioned nylon composite material.
[0006] According to the first aspect of the present application, a low-temperature crack-resistant nylon composite material is provided, which comprises the following components by weight: 43 to 60 parts of nylon resin, 8 to 15 parts of toughening agent, 30 to 40 parts of glass fiber, 0.3 to 0.5 parts of antioxidant, 0.3 to 0.5 parts of light stabilizer, and 0.5 to 2 parts of lubricant;
[0007] Wherein, the nylon resin includes one or more of PA612 and PA66.
[0008] In some of the embodiments, the mass ratio of the nylon resin, the toughening agent and the glass fiber is (43-60): (10-15): (30-35).
[0009] In some embodiments, the toughening agent includes one or more of maleic anhydride grafted ethylene-octene copolymer and ethylene-methyl acrylate-glycidyl methacrylate random terpolymer.
[0010] In some embodiments, the glass fibers have an average diameter of 9 μm to 11 μm and an average length of 2 mm to 4 mm.
[0011] In some embodiments, the glass fiber is E-type glass fiber.
[0012] In some embodiments, the antioxidant includes one or more of a hindered phenol antioxidant, a metal deactivator, a phosphite antioxidant, a hindered amine antioxidant, and a benzofuranone derivative antioxidant.
[0013] In some embodiments, the lubricant includes one or more of montan wax, polyethylene wax, ethylene acrylic acid copolymer wax and inorganic lubricant.
[0014] In some embodiments, the light stabilizer includes one or more of a hindered amine light stabilizer and an ultraviolet absorption light stabilizer.
[0015] According to a second aspect of the present application, a method for preparing a low-temperature crack-resistant nylon composite material is provided, comprising the following steps:
[0016] Mixing the components of the above-mentioned low-temperature crack-resistant nylon composite material to obtain a mixture;
[0017] The mixture is melt blended and extruded.
[0018] According to a third aspect of the present application, a nylon product is provided, comprising the above-mentioned low-temperature crack-resistant nylon composite material.
[0019] Compared with the traditional technology, this application has the following beneficial effects:
[0020] The present application adopts a specific type of nylon resin, which cooperates with a specific content of toughening agent, glass fiber, antioxidant, light stabilizer and lubricant; so that the prepared nylon composite material can not only meet the application requirements of thin-wall, but also has good anti-cracking performance under low temperature conditions. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0023] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0024] In the present application, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0027] In a first aspect of the present application, a low-temperature crack-resistant nylon composite material is provided, which comprises the following components by weight: 43 to 60 parts of nylon resin, 8 to 15 parts of toughening agent, 30 to 40 parts of glass fiber, 0.3 to 0.5 parts of antioxidant, 0.3 to 0.5 parts of light stabilizer, and 0.5 to 2 parts of lubricant;
[0028] Wherein, the nylon resin is PA612 or PA66.
[0029] The present application adopts the above-mentioned specific type of nylon resin, which is matched with specific contents of toughening agent, glass fiber, antioxidant, light stabilizer and lubricant; so that the obtained nylon composite material can not only meet the application requirements of thin-wall, but also has good anti-cracking performance under low temperature conditions.
[0030] In some embodiments, the above-mentioned low-temperature crack-resistant nylon composite material is composed of the following components: 43 parts to 60 parts of nylon resin, 8 parts to 15 parts of toughening agent, 30 parts to 40 parts of glass fiber, 0.3 parts to 0.5 parts of antioxidant, 0.3 parts to 0.5 parts of light stabilizer, and 0.5 parts to 2 parts of lubricant.
[0031] As an example, the mass fraction of nylon resin can be 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, or any value within the range formed by any two of the above point values.
[0032] Furthermore, the mass fraction of the nylon resin is 50 parts to 60 parts; furthermore, the mass fraction of the nylon resin is 55 parts to 60 parts.
[0033] As an example, the mass fraction of the toughening agent can be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, or any value within the range formed by any two of the above point values.
[0034] Furthermore, the mass fraction of the toughening agent is 10 parts to 15 parts; further, the mass fraction of the toughening agent is 12 parts to 15 parts.
[0035] In some embodiments, the mass ratio of nylon resin, toughening agent and glass fiber is (50-60): (10-15): (30-35). By adjusting the mass ratio of nylon resin, toughening agent and glass fiber within the above specific range, the synergistic effect of the three can further improve the low-temperature anti-cracking performance and impact resistance of the nylon composite material.
[0036] In some embodiments, the toughening agent includes one or more of maleic anhydride grafted ethylene-octene copolymer and ethylene-methyl acrylate-glycidyl methacrylate random terpolymer. By using the above specific types of toughening agents in combination with nylon resin, glass fiber and other components, a nylon composite material with good anti-cracking performance and impact resistance under low temperature conditions can be prepared.
[0037] Furthermore, the toughening agent is selected from maleic anhydride grafted ethylene-octene copolymer.
[0038] As an example, the mass fraction of glass fiber can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, or any value within the range formed by any two of the above point values.
[0039] In some embodiments, the glass fibers have an average diameter of 9 μm to 11 μm and an average length of 2 mm to 4 mm.
[0040] As an example, the average diameter of the glass fiber can be 9.0μm, 9.1μm, 9.2μm, 9.3μm, 9.4μm, 9.5μm, 9.6μm, 9.7μm, 9.8μm, 9.9μm, 10.0μm, 10.1μm, 10.2μm, 10.3μm, 10.4μm, 10.5μm, 10.6μm, 10.7μm, 10.8μm, 10.9μm, 11.0μm, or any value within the range formed by any two of the above point values.
[0041] Furthermore, the average diameter of the glass fibers is 10 μm.
[0042] As an example, the average length of the glass fiber can be 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.0 mm, or any value within the range formed by any two of the above point values.
[0043] Furthermore, the average length of the glass fibers is 3 mm.
[0044] In some embodiments, the glass fiber is E-type glass fiber. Adding the above-mentioned specific mass fraction of E-type glass fiber can effectively improve the impact resistance of the nylon composite material; specifically, the glass fiber can form a skeleton structure in the nylon matrix, and when the material is impacted, the glass fiber can absorb and disperse part of the energy, thereby reducing the expansion of cracks and the damage of the material.
[0045] As an example, the mass fraction of the antioxidant can be 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, or any value within the range formed by any two of the above point values.
[0046] Furthermore, the weight percentage of the antioxidant is 0.4 to 0.5 parts.
[0047] In some embodiments, the antioxidant includes one or more of a hindered phenol antioxidant, a metal deactivator, a phosphite antioxidant, a hindered amine antioxidant, and a benzofuranone derivative antioxidant.
[0048] Furthermore, the antioxidant includes a hindered amine antioxidant and a phosphite antioxidant. Furthermore, the mass ratio of the hindered amine antioxidant to the phosphite antioxidant is 1:1.
[0049] Adding the above antioxidants to nylon composite materials can effectively capture free radicals, prevent the chain of oxidation reactions, slow down the oxidation rate of nylon materials, maintain the integrity and stability of their molecular chains, enable the material to better withstand external forces when impacted or dropped, and reduce the generation and expansion of cracks.
[0050] As an example, the mass fraction of the lubricant can be 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, or any value within the range formed by any two of the above point values.
[0051] Furthermore, the mass fraction of the lubricant is 0.4 to 0.5 parts.
[0052] In some embodiments, the lubricant includes one or more of montan wax, polyethylene wax (ie, PE wax), ethylene acrylic acid copolymer wax (ie, EAA wax), and an inorganic lubricant.
[0053] The above lubricants can improve the toughness of nylon materials, so that the materials can undergo a certain degree of plastic deformation instead of brittle fracture when impacted.
[0054] Further, the lubricant is selected from polyethylene wax. It is understandable that selecting polyethylene wax as a lubricant can further improve the low-temperature anti-cracking performance and impact resistance of the nylon composite material.
[0055] As an example, the mass fraction of the light stabilizer can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, or any value within the range formed by any two of the above point values.
[0056] Furthermore, the mass fraction of the light stabilizer is 1 to 2 parts.
[0057] In some embodiments, the light stabilizer includes one or more of a hindered amine light stabilizer and an ultraviolet light stabilizer.
[0058] Furthermore, the light stabilizer includes a hindered amine light stabilizer and an ultraviolet absorption light stabilizer; further, the mass ratio of the hindered amine light stabilizer to the ultraviolet absorption light stabilizer is 1:1.
[0059] In some embodiments, the nylon composite material includes the following components, measured by weight: 50 to 60 parts of nylon resin, 10 to 15 parts of toughening agent, 30 to 35 parts of glass fiber, 0.4 to 0.5 parts of antioxidant, 0.4 to 0.5 parts of light stabilizer, and 1 to 2 parts of lubricant.
[0060] In some embodiments, the above-mentioned low-temperature crack-resistant nylon composite material is composed of the following components, measured by weight: 50 to 60 parts of nylon resin, 10 to 15 parts of toughening agent, 30 to 35 parts of glass fiber, 0.4 to 0.5 parts of antioxidant, 0.4 to 0.5 parts of light stabilizer, and 1 to 2 parts of lubricant.
[0061] In a second aspect of the present application, a method for preparing a low-temperature crack-resistant nylon composite material is provided, comprising S10 to S20:
[0062] S10: Mix the components of the above-mentioned low-temperature crack-resistant nylon composite material to obtain a mixture.
[0063] S20: melt-blending and extruding the mixture.
[0064] In a third aspect of the present application, a nylon product is provided, comprising the above-mentioned low-temperature crack-resistant nylon composite material.
[0065] The above-mentioned nylon products can be used as automotive accessories, home appliance accessories, aerospace components, and equipment accessories suitable for low-temperature scenarios, etc.
[0066] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0067] Example 1
[0068] (1) Provide the following components by weight: 60 parts of nylon resin, 8 parts of toughening agent, 30 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0069] (2) The above components are mixed, fed into the main feeding system of an extruder, melt blended at 280°C, and extruded and granulated at 270°C to obtain a nylon composite material resistant to low-temperature cracking.
[0070] Among them, the nylon resin is nylon 66, with a relative viscosity of 2.7, purchased from Shenma. The toughening agent is maleic anhydride grafted ethylene-octene copolymer, purchased from Dow Chemical; the glass fiber is E-type glass fiber with a diameter of 10μm and a length of 3mm; the antioxidant is a mixture of hindered amine antioxidants and phosphite antioxidants in a weight ratio of 1:1, purchased from BASF; the light stabilizer is a mixture of hindered amine light stabilizers and ultraviolet absorption light stabilizers in a weight ratio of 1:1, purchased from BASF; the lubricant is polyethylene wax AC540A, purchased from Honeywell.
[0071] Example 2
[0072] It is basically the same as Example 1, except that the mass fractions of each component are different.
[0073] (1) The nylon composite material in Example 2 includes the following components: 53 parts of nylon resin, 15 parts of toughening agent, 30 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0074] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0075] Example 3
[0076] It is basically the same as Example 1, except that the mass fractions of each component are different.
[0077] (1) The nylon composite material in Example 3 includes the following components: 50 parts of nylon resin, 8 parts of toughening agent, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0078] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0079] Example 4
[0080] It is basically the same as Example 1, except that the mass fractions of each component are different.
[0081] (1) The nylon composite material in Example 4 includes the following components: 43 parts of nylon resin, 15 parts of toughening agent, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0082] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0083] Example 5
[0084] It is basically the same as Example 1, except that the type of nylon resin is different.
[0085] (1) Example 5 uses an equal amount of nylon 612 to replace nylon 66. The relative viscosity of nylon 612 is 2.4.
[0086] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0087] Example 6
[0088] It is basically the same as Example 5, except that the mass fractions of each component are different.
[0089] (1) The nylon composite material in Example 6 includes the following components: 53 parts of nylon resin, 15 parts of toughening agent, 30 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0090] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0091] Example 7
[0092] It is basically the same as Example 5, except that the mass fractions of each component are different.
[0093] (1) The nylon composite material in Example 7 includes the following components: 50 parts of nylon resin, 8 parts of toughening agent, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0094] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0095] Example 8
[0096] It is basically the same as Example 5, except that the mass fractions of each component are different.
[0097] (1) The nylon composite material in Example 8 includes the following components: 43 parts of nylon resin, 15 parts of toughening agent, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0098] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0099] Example 9
[0100] It is basically the same as Example 8, except that the type of lubricant is different; specifically, Example 9 uses an equal mass fraction of N,N'-ethylene bisstearamide (EBS) instead of polyethylene wax.
[0101] Comparative Example 1
[0102] It is basically the same as Example 1, except that no toughening agent is included and the mass fractions of each are different.
[0103] (1) The nylon composite material in Comparative Example 1 includes the following components: 68 parts of nylon resin, 30 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0104] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0105] Comparative Example 2
[0106] It is basically the same as Example 1, except that no toughening agent is included and the mass fractions of each are different.
[0107] (1) The nylon composite material in Comparative Example 2 includes the following components: 58 parts of nylon resin, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0108] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0109] Comparative Example 3
[0110] It is basically the same as Example 5, except that no toughening agent is included and the mass fractions of each are different.
[0111] (1) The nylon composite material in Comparative Example 3 includes the following components: 68 parts of nylon resin, 30 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0112] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0113] Comparative Example 4
[0114] It is basically the same as Example 5, except that no toughening agent is included and the mass fractions of each are different.
[0115] (1) The nylon composite material in Comparative Example 4 includes the following components: 58 parts of nylon resin, 40 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of lubricant.
[0116] (2) The above components are mixed and fed into the main feeding system of an extruder for melt blending and extrusion granulation to obtain a nylon composite material that is resistant to low-temperature cracking.
[0117] The nylon composite materials of the above-mentioned embodiment and comparative example were respectively made into thin-walled materials with a thickness of 1 mm and 4 mm and a rectangular shape by injection molding.
[0118] The composition ratios of the nylon composite materials of the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Table 1; the performance data of the thin-walled materials made of the nylon composite materials in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 2. Among them, the -40°C impact strength is obtained by referring to the ISO179 test standard; the resistance to deformation at 150°C is obtained by referring to the ISO 75-2 test standard; and the tensile strength is obtained by referring to the ISO527-2 test standard. The -40°C impact strength, the resistance to deformation at 150°C and the tensile strength are tested using a standard test strip with a thickness of 4mm. The ball drop performance is tested at -40°C using a 500g ball dropped from a height of 1m onto a plate with a thickness of 1mm.
[0119] Table 1
[0120]
[0121] Table 2
[0122]
[0123] In Table 2, "NB" means "Not Broken" or "Not Broken", indicating that the nylon composite material did not break after being subjected to the specified impact energy or impact method.
[0124] It can be seen from Examples 1 to 4 that if no toughening agent is added to the components of the nylon composite material, its low-temperature anti-cracking performance will be significantly reduced. Compared with Examples 1 and 3, the amount of toughening agent in Examples 2 and 4 is increased, and the nylon composite material finally obtained does not crack at -40°C; this shows that increasing the content of the toughening agent can further improve the low-temperature anti-cracking performance of the nylon composite material.
[0125] It can be seen from Examples 1 and 3 that reducing the glass fiber content and increasing the nylon resin content will further improve the anti-cracking performance of the nylon composite material.
[0126] It can be seen from Examples 1 and 5, and Examples 3 and 7 that, when the mass fractions of the components are the same, selecting PA612 as the nylon resin can further improve the anti-cracking performance of the nylon composite material.
[0127] It can be seen from Examples 8 and 9 that, compared with N,N'-ethylene bisstearamide, the present application uses polyethylene wax as a lubricant, which can further improve the low-temperature impact resistance and tensile strength of the nylon composite material.
[0128] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0129] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A low temperature crack resistant nylon composite material, characterized in that: The composition includes the following components by weight: 43 to 60 parts of nylon resin, 8 to 15 parts of toughening agent, 30 to 40 parts of glass fiber, 0.3 to 0.5 parts of antioxidant, 0.3 to 0.5 parts of light stabilizer, and 0.5 to 2 parts of lubricant; Wherein, the nylon resin includes one or more of PA612 and PA66.
2. The low temperature crack resistant nylon composite material according to claim 1, characterized in that: The mass ratio of the nylon resin, the toughening agent and the glass fiber is (43-60): (10-15): (30-35).
3. The low temperature crack resistant nylon composite material according to any one of claims 1 to 2, characterized in that: The toughening agent includes one or more of maleic anhydride grafted ethylene-octene copolymer and ethylene-methyl acrylate-glycidyl methacrylate random terpolymer.
4. The low temperature crack resistant nylon composite material according to any one of claims 1 to 2, characterized in that: The glass fibers have an average diameter of 9 μm to 11 μm and an average length of 2 mm to 4 mm.
5. The nylon composite material according to claim 4, characterized in that: The glass fiber is E-type glass fiber.
6. The low temperature crack resistant nylon composite material according to any one of claims 1 to 2 and 5, characterized in that: The antioxidant includes one or more of hindered phenol antioxidants, metal deactivators, phosphite antioxidants, hindered amine antioxidants and benzofuranone derivative antioxidants.
7. The low temperature crack resistant nylon composite material according to any one of claims 1 to 2 and 5, characterized in that: The lubricant includes one or more of montan wax, polyethylene wax, ethylene acrylic acid copolymer wax and inorganic lubricant.
8. The low temperature crack resistant nylon composite material according to any one of claims 1 to 2 and 5, characterized in that: The light stabilizer includes one or more of hindered amine light stabilizers and ultraviolet absorption light stabilizers.
9. A method for preparing a low-temperature crack-resistant nylon composite material, characterized in that: The following steps are involved: Mixing the components of the low-temperature crack-resistant nylon composite material according to any one of claims 1 to 8 to obtain a mixture; The mixture is melt blended and extruded.
10. A nylon product, characterized in that: The invention comprises the low temperature crack resistant nylon composite material as described in any one of claims 1 to 8.